STRATEGI PENGEMBANGAN USAHA MINUMAN BARJAZ TEA DI BARJAZ COMPANY - Anik Mas Juliani, Ketut; Harsojuwono, Bambang Admadi; Satriawan, Ketut (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2017)
This research aimed to analyze the internal and external conditions, to formulate strategies, and to determine the priorities of Barjaz Tea business development. Business development strategy is determined by using SWOT (Strength, Weakness, Oppurtunities, and Threats) matrix analysis, quantitative analysis using EFE, IFE and IE matrix, and also strategy priority analysis using TOPSIS (Technique for Order of Preference by Similarity to Ideal Solution ) method. The research results show that there were 7 strengths, 6 weaknesses, 5 opportunities and 2 threats in this business. The value of the IFE (Internal Factor Evaluation) matrix analysis was 3.216 and the EFE (External Factor Evaluation) matrix was ??3.151. These values indicate a strong position, in the IE (Internal External) matrix strategies that should be to develop are consisting of intensive strategy (market penetration, market development and product development), and integrative strategy (backward integration, forward integration and integration horizontal). Based on SWOT analysis there were alternative strategies that can be recommended to develop Barjaz Tea business. TOPSIS analysis results with the value of the proximity of each alternative to the ideal solution was 1.000, namely maximize the availibility of raw materials. Keywords : business development strategy, Barjaz tea, SWOT, TOPSIS.